Geotechnical performance of municipal solid waste fines stabilized with xanthan gum and agar gum - Verma A.K.; Prasad A.; Bonal N.S. (My University, 2025)
This study investigates the geotechnical performance of municipal solid waste fines (MSWF) stabilized with xanthan gum and agar gum. As urbanization escalates, the challenge of managing MSW becomes more critical, especially in India, projected to produce up to 436 million tonnes annually by 2050. Landfill mining yields material with poor engineering properties, necessitating effective stabilization techniques. This research evaluates the efficacy of xanthan and agar gums in enhancing the geotechnical properties of MSW fines. Various tests, including compaction, triaxial, and unconfined compressive strength, were conducted on samples subjected to different curing periods. The results indicate a substantial improvement in the mechanical properties of MSW fines treated with agar gum, including a maximum increase of 58% in unconfined compressive strength (UCS). Microstructural examinations confirm enhanced interparticle bonding, while leachate analysis shows a notable reduction in heavy metal release. Statistical assessments underscore the significance of curing time in determining the final properties of the treated MSW fines. Overall, agar gum emerges as a more effective biopolymer for MSW fines stabilization, with curing duration playing a vital role in achieving optimal geotechnical characteristics. These findings offer valuable insights for selecting appropriate bio-treatment methods for heterogeneous materials like MSW fines. © The Author(s), under exclusive licence to Springer Nature Japan KK, part of Springer Nature 2024.